Defining the frontiers between antifungal resistance, tolerance and the concept of persistence. (November 2015) - Delarze, Eric; Sanglard, Dominique
Abstract: A restricted number of antifungal agents are available for the therapy of fungal diseases. With the introduction of epidemiological cut-off values for each agent in important fungal pathogens based on the distribution of minimal inhibitory concentration (MIC), the distinction between wild type and drug-resistant populations has been facilitated. Antifungal resistance has been described for all currently available antifungal agents in several pathogens and most of the associated resistance mechanisms have been deciphered at the molecular level. Clinical breakpoints for some agents have been proposed and can have predictive value for the success or failure of therapy. Tolerance to antifungals has been a much more ignored area. By definition, tolerance operates at antifungal concentrations above individual intrinsic inhibitory values. Important is that tolerance to antifungal agents favours the emergence of persister cells, which are able to survive antifungal therapy and can cause relapses. Here we will review the current knowledge on antifungal tolerance, its potential mechanisms and also evaluate the role of antifungal tolerance in the efficacy of drug treatments.